1995
DOI: 10.1254/jjp.68.103
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gastric Function and Healing of Chronic Gastric Ulcers in Aged Rats

Abstract: ABSTRACT-The present study was designed to determine the relationship between changes in gastric function caused by aging and the healing of gastric ulcers. Male Fischer-344 rats (young, 2 months; aged, 24-26 months) were used. Gastric ulcers were induced by luminal application of an acetic acid solution (60%, 0.2 ml, 45 sec). The basal and histamine-stimulated gastric acid secretions in aged animals were significantly lower than those in young animals. However, the serum gastrin levels were almost the same in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Tsukimi and Okabe 18 have reported that ageing does not significantly affect the development and healing rate of acetic acid‐induced gastric ulcers in rats. They suggested that this could be explained by the counterbalance of positive and negative components for ulcer healing.…”
Section: Discussionmentioning
confidence: 99%
“…Tsukimi and Okabe 18 have reported that ageing does not significantly affect the development and healing rate of acetic acid‐induced gastric ulcers in rats. They suggested that this could be explained by the counterbalance of positive and negative components for ulcer healing.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its lack of adhesion, the mounting of stomachs with Type 3 ulcers to Lucite chambers is easier than with Type 1 or Type 2 ulcers. Our group 22) also examined the changes in gastric function and healing of acetic acid gastric ulcers in older rats. We found that aging had little or no influence on the development and healing rate of gastric ulcers, but the quality of ulcer healing was quite different between younger (2 month old) and older (24-26 month old) rats.…”
Section: Type 3 Ulcer Modelmentioning
confidence: 99%
“…Experimental and limited clinical studies indicate that aging gastric mucosa has impaired mucosal defenses such as decreased mucus and bicarbonate secretion,17-19 decreased prostaglandin generation,15,20,21 reduced nitric oxide synthase activity,17,22 and reduced blood flow 23,24. Furthermore, aging increases the susceptibility to injury by a variety of damaging agents such ethanol7,23 as well as NSAIDs,25,26 and also impairs the healing of acute injury and chronic gastric ulcers 15,27…”
Section: Introductionmentioning
confidence: 99%